Is Opioid Prescribing Driving Trauma Recidivism or is Trauma Driving Opioid Use?. Issue 6 (June 2019) - Harmon, Laura; Sukri, Leah; Kufera, Joseph A.; Nguyen, Andrew; Grunnagle, Meilin; Ramirez, Christine L.; Botwinick, Isadora; Cucher, Daniel; Feather, Cristina B.; Scalea, Thomas M.; Stein, Deborah M.
In the past 30 years, opioid prescription rates have quadrupled and hospital admissions for overdose are rising. Previous studies have focused on alcohol use and trauma recidivism, however rarely evaluating recidivism and opioid use. We hypothesized there is an association between opioid use and trauma recidivism. This is a retrospective review of patients with multiple admissions for traumatic injury. Demographics, opioid toxicology screen (TS) results, and injury characteristics were collected. Statistical analysis was performed with chi-squared and Poisson regression models. One thousand six hundred forty-nine patients (age ≥18 years) had multiple trauma admissions. Seven hundred nine patients had TS data for both admissions. Thirty-one per cent (218) were TS positive on the 1st admission compared with 34 per cent (244) on their 2nd admission. Fifty-five per cent of patients who were TS positive on the 1st admission were positive on their 2nd admission, whereas 25 per cent who were TS negative on the 1st admission were subsequently positive on their 2nd admission ( P < 0.0001). Patients who were TS positive on the subsequent admission were less severely injured than TS negative patients (Injury Severity Score > 15, 26.3% vs 22.3%, P = 0.04). The only significant risk factor for being TS positive on the 2nd admission was being TS positive on the 1st admission (relative risk = 2.18, P < 0.001). A previous history of opioid use is the strongest predictor of recurrent use in recidivists.